Data on species composition and Distribution of land snail’s fauna (Gastropoda) on Nui Voi hill, An Lao district, Hai Phong province - Nhuong, Do Van; Minh, Ngo Thi (Academia Journal of Biology, 2012)
In this report, we provide information about composition species, distribution of land snails and difference of them about habitats and topographies on Nui Voi, Hai Phong. Based on analysis of land snail samples collected from Nui Voi hill in Hai Phong province, research results show that land snail fauna has 36 species belong to 28 genera, 14 families, 4 orders (Neritopsina, Architaenioglossa, Archaeopulmonata and Stylommatophora) and 2 subclasses Prosobranchia and Pulmonata. In which, Pulmonata occupied 72.2% of total recorded species in survey area. The most in number of species in Cyclophoridae, Ariophantidae, Camaenidae and Subulinidae. Distribution about habitat is very different. Number of landsnail species on the limestone mountains is more abundant than on feralit soil mountains. In this species composition, some species (Opeas pyrgula, O. gracilia, O. filare, Diplommatina herziana, Coniglobus albius and Cyclophorus siamensis) were also recorded on many islands in the Western Pacific Ocean region. Preliminary comments show that the landsnails fauna on this area close to fauna of many islands in the western Pacific Ocean (Hainan island, the Philippines, Malaysia...).